METHODOLOGICAL FOUNDATIONS OF FORMATION OF ETHONOCULTURAL COMPETENCE OF PERSONALITY - Berezyuk, Olena S. (Educological discourse, 2015)
The article deals with the methodological foundations of the formation of ethno-cultural competence of the personality. The mechanism of ethnic culture and its main function are analyzed. The article shows stages of ethno-cultural competence levels of a person, underlines the basic techniques, forms, its means of implementation in the educational process.